On the Sources of Oil Price Fluctuations - Unalmis, Deren; Unalmis, Ibrahim; Unsal, Filiz (Washington, D.C. : International Monetary Fund, 2009)
Analyzing macroeconomic impacts of oil price changes requires first to investigate different sources of these changes and their distinct effects. Kilian (2009) analyzes the effects of an oil supply shock, an aggregate demand shock, and a precautionary oil demand shock. The paper's aim is to model macroeconomic consequences of these shocks within a new Keynesian DSGE framework. It models a small open economy and the rest of the world together to discover both accompanying effects of oil price changes and their international transmission mechanisms. Our results indicate that different sources of oil price fluctuations bring remarkably diverse outcomes for both economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet